Associations Between Dysphagia and Adverse Health Outcomes in Older Adults with Dementia in Intensive Care Units: A Retrospective Cohort Study - Cheng H; Deng X; Li J; Tang Y; Yuan S; Huang X; Wang Z; Zhou F; Lyu J (Clinical Interventions in Aging, 2023)
Hongtao Cheng,1,2,* Xingwen Deng,3,* Jieyao Li,4,* Yonglan Tang,1,2 Shiqi Yuan,5 Xiaxuan Huang,5 Zichen Wang,1 Fuling Zhou,6 Jun Lyu1,7 1Department of Clinical Research, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 2School of Nursing, Jinan University, Guangzhou, People’s Republic of China; 3Department of Medical Information, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 4Department of Intensive Care Unit, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 5Department of Neurology, The First Affiliated Hospital of Jinan University, Guangzhou, People’s Republic of China; 6Department of Hematology, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 7Guangdong Provincial Key Laboratory of Traditional Chinese Medicine Informatization, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Lyu, Department of Clinical Research, The First Affiliated Hospital of Jinan University, Guangzhou, 510630, People’s Republic of China, Email lyujun2020@jnu.edu.cn Fuling Zhou, Department of Hematology, Zhongnan Hospital of Wuhan University, No. 169 Donghu Road, Wuhan, 430071, People’s Republic of China, Email zhoufuling@whu.edu.cnBackground: Dysphagia is common in elderly patients with dementia and is one of the common clinical geriatric syndromes. It imposes a heavy burden on patients and their caregivers and is becoming an important public health problem. This study examined the association between dysphagia in older dementia patients in the ICU and the subsequent adverse health outcomes they experience.Patients and Methods: A retrospective analysis of adults (≥ 65 years) with dementia in ICUs of a Boston tertiary academic medical center was conducted. Using the International Classification of Diseases’ Ninth and Tenth Revisions, dementia patients were identified. The study cohort comprised 1009 patients, median age 84.82 years, 56.6% female, predominantly White (72.9%). Patients were grouped based on swallowing function: dysphagia (n=282) and no-dysphagia (n=727). Dysphagia was identified via positive bedside swallowing screening. Primary outcomes were 90- and 180-day mortality, secondary outcomes included aspiration pneumonia, pressure injury, and delirium. Cohort characteristics were compared using the Wilcoxon rank-sum and chi-square tests. Dysphagia and outcomes correlations were examined via Kaplan-Meier survival analysis, Cox proportional-hazards regression models, logistic regression models, and subgroup analysis.Results: After adjusting for covariates, the results from multivariate Cox proportional-hazards regression indicated that dysphagia was significantly associated with increased 90-day (HR=1.36, 95% CI=1.07– 1.73, E-value=1.78) and 180-day (HR=1.47, 95% CI=1.18– 1.82, E-value=1.94) mortality; the multifactorial logistic regression results indicated that dysphagia was associated with significant increases in pressure injury (OR=1.58, 95% CI=1.11– 2.23, E-value=1.83) and aspiration pneumonia occurrence (OR=4.04, 95% CI=2.72– 6.01, E-value=7.54), but was not significantly associated with delirium prevalence (OR=1.27, 95% CI=0.93– 1.74).Conclusion: Dysphagia is likely to increase the risk of adverse health outcomes in older adults with dementia in ICU, and these adverse outcomes mostly include 90- and 180-day mortality, aspiration pneumonia, and pressure injury.Keywords: dysphagia, dementia, older adults, mortality, intensive care unit, delirium